Design and Implementation of Engine Order Telegraph With RS485 Communication for Ship Maneuvering - Slamet Winardi; Sri Mulyanto Herlambang; Frengki Imanto; Arief Budijanto (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2023)
EOT (Engine Order Telegraph) is the embodiment of a machine-human interface that is controlled by the captain of the ship for safe and sustainable ship maneuvers as a basic part of a connected remote propulsion system. Remote control systems on modern ships usually have a control transfer system that allows control to be transferred between locations. Remote control is usually possible from two locations: the platform and the Engine Control Room (ECR). Some ships do not have a remote control handle on the ECR. When in bridge control mode, the bridge handle directly controls the engine set point. When in Engine Control Room mode, the bridge handle sends a telegraph signal to the ECR and the ECR handle controls the control system set point. In local control, the remote control system is inactive and the bridge handle sends a telegraph signal to the local control position and the machine is operated by its manual control in the engine room. In this study, an EOT device will be realized using the Arduino Mega2560 microcontroller and data communication using the RS485 serial from the bridge to the engine control room.